A note on equilibrium Glauber and Kawasaki dynamics for permanental point processes - Lytvynov, E. W.; Li, Guanhua (Methods of Functional Analysis and Topology, 2011)
We construct two types of equilibrium dynamics of an infinite particle system in a locally compact metric space X for which a permanental point process is a symmetrizing, and hence invariant measure. The Glauber dynamics is a birth-and-death process in X, while in the Kawasaki dynamics interacting particles randomly hop over X. In the case X=R^d, we consider a diffusion approximation for the Kawasaki dynamics at the level of Dirichlet forms. This leads us to an equilibrium dynamics of interacting Brownian particles for which a permanental point process is a symmetrizing measure.